Ação conjugada de laser e liberação miofascial nos processos inflamatórios e degenerativos do ombro: estudo piloto - Canelada, Ana Carolina Negraes (2022)
The shoulder is a very complex joint, considered the most mobile in the entire human body and to maintain the normal biomechanics of the joint it is necessary that all structures are in sync. If these structures show alterations, the joint complex will be the target of numerous conditions, including the Impact Syndrome (IOI). This, in turn, is characterized by mechanical impaction or compression of certain structures, which may present inflammation, degeneration in the tendons, as is the case with tendinopathy, and changes in the joint capsule, as is the case with Adhesive Capsulitis. For this purpose, an equipment capable of promoting myofascial release synergistically with the action of the laser was developed, with the objective of comparing the isolated actions of photobiomodulation and the performance of the myofascial release technique, in relation to the conjugated action of the same, analyzing possible changes between the therapies used in relation to pain and changes in the condition of carrying out the movements, in the inflammatory and degenerative processes using respectively the goniometric measurement of the joint angles, the visual analogue scale and the Questionnaire of Dysfunctions of the Arm, Shoulder and hand. According to the results obtained, the interventions were able to induce a positive effect on the symptoms of the pathologies, but the combined interventions resulted in a greater significant difference, thus reducing the treatment time to 35 days, and after 60 days of the evolution of the disease. treatment, the combined action made it possible to maintain the patient's improvement, thus allowing a full restoration of movements and absence of pain. It is concluded, therefore, that the combined interventions resulted in a greater significant difference and the maintenance of the patient's improvement, both in relation to pain and limitation of movements, and can be used as an alternative non-pharmacological treatment, promoting well-being. and quality of life for the patient.